Sosialisasi Pembuatan Puding Daun Kelor (DAUKEL) Di Desa Rukma Jaya - Ellayuni Nur Fadila; Yesi Mariska; Adrian Rizky Rahmawan; Ade Galih Putra Ashari; Hamdan Mustameer; Zainal Abidin Achmad (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
Increasing awareness of the importance of a healthy diet and nutrition for rural communities is the main goal of the XI 2023 National Service Service project. In this context, this journal documents community service efforts in Rukma Jaya Village through the outreach program for making Moringa Leaf Pudding (DAUKEL). Moringa leaves as a source of nutrients that are rich in essential substances, are the main focus of this program. Villagers, especially housewives, are invited to recognize the benefits of Moringa leaves and integrate them into their daily diet through creative innovations such as Moringa leaf pudding. The active participation of the community in this activity is a driving force in achieving program objectives. The results of this journal provide an overview of the effectiveness of a practical and participatory approach in conveying important messages about nutrition and healthy eating patterns to rural communities. The socialization of making Moringa leaf pudding (DAUKEL) not only creates awareness, but also provides insight into the diversification of local food ingredients that are nutritious and environmentally friendly